Inhibition of Wnt pathway activity as a treatment approach for human osteoarthritis: a systematic review - Eli T. Sayegh; Molly Zgoda; Chilan B.G. Leite; Andrea C. Carrano; Jeyanesh Tambiah; Christian Lattermann (Elsevier, 2022)
Background: Osteoarthritis (OA) is a chronic, degenerative condition associated with joint pain and disability. Because Wnt pathway signaling activity is abnormally upregulated in preclinical OA models, its inhibition is a target for disease-modifying OA drugs. Objectives: The literature was systematically reviewed for disease-modifying effects of Wnt pathway-inhibiting molecules in preclinical animal models and human subjects with OA. Data sources: Cochrane Database of Systematic Reviews, Pubmed, and Embase were searched using the terms: Wnt inhibitor, Wnt inhibition, catenin, osteoarthritis, and arthritis. Study eligibility criteria, participants, and interventions: Inclusion criteria were English-language preclinical (mammal) or human studies on OA disease modification; pharmacologic or genetic Wnt-pathway inhibition; and reporting of clinically relevant endpoints. Study appraisal and synthesis methods: Independent data abstraction from eligible studies by 2 authors. Results: Forty-nine studies were included, of which 46 studies examined in-vivo Wnt pathway inhibition in animal models via pharmacologic or genetic means, and 3 studies focused on human subjects with knee OA. Limitations: Nearly all included articles studied knee OA. Certain naturally occurring Wnt inhibitors possess nonspecific activity against other processes. Data from young rodents may not reflect disease progression in human OA. In animal models, surgical OA induction represents a post-traumatic OA model, while chemical OA induction may not mimic the natural pathogenesis and disease progression in humans. Conclusions and implications of key findings: The literature suggests pharmacologic Wnt modulators have biological activity against the OA disease cascade with potential for therapeutic development in humans. Systematic review registration number: Not applicable.